2016
DOI: 10.1209/0295-5075/114/60010
|View full text |Cite
|
Sign up to set email alerts
|

Relation between irreversibility and entanglement in classically chaotic quantum kicked rotors

Abstract: The relation between the degree of entanglement and time scale of time-irreversible behavior is investigated for classically chaotic quantum coupled kicked rotors by comparing the entanglement entropy (EE) and the lifetime of correspondence with classical decay of correlation, which was recently introduced. Both increase on average drastically with a strong correlation when the strength of coupling between the kicked rotors exceeds a certain threshold. The EE shows an anomalously large fluctuation resembling a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…As stated above, even a partly chaotic phase space is enough to have Arnold diffusion, and this fact translates in a diffusive long-term dynamics, possibly after a transient [36,5,37,38,7]. In the quantum case the behavior is different and dynamical localization can persist for a finite number of rotors [39,40,41,42,43]. Nevertheless, it disappears in the thermodynamic limit, when the number of rotors tends to infinity [39] (although it can persist in the thermodynamic limit in other systems [44,45]).…”
Section: Introductionmentioning
confidence: 99%
“…As stated above, even a partly chaotic phase space is enough to have Arnold diffusion, and this fact translates in a diffusive long-term dynamics, possibly after a transient [36,5,37,38,7]. In the quantum case the behavior is different and dynamical localization can persist for a finite number of rotors [39,40,41,42,43]. Nevertheless, it disappears in the thermodynamic limit, when the number of rotors tends to infinity [39] (although it can persist in the thermodynamic limit in other systems [44,45]).…”
Section: Introductionmentioning
confidence: 99%
“…As has been discussed in detail in the previous paper [19], the short saturation time means that in a single KR the number of eigenstates which are significantly connected with an eigenstate by the interaction potential ηqf ( Î) cos ωt in Eq. ( 1) is much less than N .…”
Section: Operation Of the Damper A Energy Transfer Processmentioning
confidence: 93%
“…With the method we can map the Fourier spectral features of correlation function to the diffusion characteristics of a fictious measurement system. Applying the method to coupled quantum chaotic rotors, we found that the time scale on which the decay-able quantum correlation is maintained is proportional to N 2 dim , not N dim if a full entanglement is achieved among the quantum chaos units [18,19]. We called this "lifetime" of the decay-able correlation.…”
Section: Introductionmentioning
confidence: 99%
“…We here make some remarks on related previous studies. The long-time average of entanglement entropy in quantum chaotic systems is known to play an essential role as an indicator of chaos [44][45][46][47][48][49][50][51][52][53][54][55][56][57][58]. In general, for initial wave packets belonging to a chaotic region in classical phase space, the longtime average of entanglement entropy is much larger than that of the regular case.…”
Section: A Long-time Averaged Entropymentioning
confidence: 99%